Psalms, Songs, and Sonnets (1611) - Byrd, William 1539/40-1623; Morehen, John; Brett, Philip (London Stainer & Bell New York Galaxy Music Corp., 1987)
Byrd himself described his last publication, Psalmes, Songs and Sonnets of 1611 as his ultimum vale. Nonetheless, some of the music was written earlier, and compiled or adapted to complete this collection of 32 pieces in three, four, five and six parts. Five of the 3-part pieces are settings of texts from the first English emblem book, Geoffrey Whitney’s A Choice of Emblems of 1586. Facsimiles of the relevant pages from Whitney are included.
Keywords: 17th Century (1601-1700); Song; Psalm; Poetry